Poorer Countries and the Environment: Friends or Foes?. (August 2015) - Broad, Robin; Cavanagh, John
Highlights: We delineate conditions when poor countries choose environment over economic ends. We examine case studies of El Salvador and Costa Rica mining bans. Research traces variables of civil society, business, and government in both. Civil society, business, and government interact to determine policy outcomes. Findings in the two countries open research for other countries and beyond mining. Summary: This article focuses on delineating the conditions under which the governments of poorer countries become active defenders and protectors of the environment. It does so based on field work in two poorer countries, El Salvador and Costa Rica, where the governments have instituted moratoria on financially lucrative but environmentally destructive mining in order to protect the environment. Building on these case studies and prior work, the article posits three conditions—related to civil society, the private sector, and the public sector—under which governments of poorer countries implement policies that favor environmental ends over shorter term economic rewards.